Neutrality of Village Heads and Village Officials in Pemilukada in Luwu Regency - Asbudi Dwi Saputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
The leadership of a Village Head in each village must be able to be a good example and role model for the community. The involvement of the Tirowali village head in Luwu Regency in practical politics in the last 2018 regional head elections is of course contrary to the provisions stipulated in the Law, this is very contrary to his position as a government official who is expected to be neutral in politics. The strategic and significant role of the Election Supervisory Agency, namely how to avoid potential election violations arises by implementing optimal prevention strategies. This study aims to determine the role and function of Bawaslu in carrying out prevention and prosecution of violations of the neutrality of village heads and to determine the factors that affect the credibility of village heads in regional head elections. This study uses a normative legal research method with a case approach which is carried out by examining cases related to the issue of the neutrality of the village head in Luwu Regency, and has become a decision that has permanent legal force. The results of this study indicate that the need to strengthen regulations to give authority to election supervisory agencies to impose sanctions on violations of neutrality in regional head elections, the involvement of village heads in practical politics indicates that government bureaucrats can still be covered by political interests.